Kajian Usaha Jamu Temulawak di Kelurahan Tanjung Rema Martapura - Dini Sri Astuty; Siti Erlina; Inda Ilma Ifada (LPPM Sekolah Tinggi Ilmu Pertanian Amuntai, 2022)
This study aims to determine the technical and prospect of making curcuma herbal medicine in Tanjung Rema Martapura Village. The research method uses analysis with descriptive, qualitative and quantitative methods so as to obtain the desired picture, related to the cost structure and income of the curcuma herbal medicine business. The results showed that the technique of making curcuma herbal drink in Tanjung Rema Village, Martapura District was still relatively traditional and simple. Based on the income value obtained by the SANI entrepreneur and the Mama Ratih entrepreneur, they are both efficient, because the R/C ratio value is > 1. The revenue from the business of making curcuma herbal drinks in one month for Sani entrepreneurs is Rp. 39,840,000 and Mama Ratih is Rp. 24,960,000. with an average of Rp.32,400,000. The income that the entrepreneur Sani receives per month is Rp. 12,888,554 and Mama Ratih is Rp. 9,167,686, for the profit of the entrepreneur Sani is Rp. 9,180,221 and Mama Ratih is Rp. 6,017,686. The prospect of developing the Curcuma Herbal Medicine Business in Tanjung Rema Martapura Village is very wide open when viewed from market demand as well as the availability of raw materials and the long term.